The Heterogeneous Effects of Conflict on Education: A Spatial Analysis in Sub-Saharan Africa - Kerstin Unfried; Krisztina Kis-Katos (Institute of Labor Economics (IZA), 2020)
In this paper, we identify under which conditions and to what extent armed conflicts harm the long-run educational attainment of children in rural Sub-Saharan Africa. By combining 66 rounds of DHS surveys with geo-coded conflict information, our study contextualizes the findings of a series of country-specific case studies on the effects of conflict on education, and provides evidence on the mechanisms through which these effects occur. Our main identification strategy compares educational losses of youth living within the same household, while also controlling for local weather shocks and countrywide dynamics in education. The effects of conflict on education are strongly context dependent. High-intensity conflicts reduce local educational attainment, on average, although this effect becomes insignificant in strong autocracies. By contrast, education is generally unaffected by localized low-intensity conflict. Human capital loss due to conflict is most severely felt in weak states, and in response to non-state based conflicts, highlighting the importance of state capacity in mediating the educational costs of local conflicts.
Keywords: I25; D74; O12; 330; education; years of schooling; conflict; Sub-Saharan Africa